Experimental signature of a topological quantum dot. Issue 44 (11th November 2020) - Rider, Marie S.; Sokolikova, Maria; Hanham, Stephen M.; Navarro-Cía, Miguel; Haynes, Peter D.; Lee, Derek K. K.; Daniele, Maddalena; Cestelli Guidi, Mariangela; Mattevi, Cecilia; Lupi, Stefano; Giannini, Vincenzo
Abstract : Topological insulator nanoparticles (TINPs) host topologically protected Dirac surface states, just like their bulk counterparts. Abstract : Topological insulator nanoparticles (TINPs) host topologically protected Dirac surface states, just like their bulk counterparts. For TINPs of radius <100 nm, quantum confinement on the surface results in the discretization of the Dirac cone. This system of discrete energy levels is referred to as a topological quantum dot (TQD) with energy level spacing on the order of Terahertz (THz), which is tunable with material-type and particle size. The presence of these discretized energy levels in turn leads to a new electron-mediated phonon-light coupling in the THz range, and the resulting mode can be observed in the absorption cross-section of the TINPs. We present the first experimental evidence of this new quantum phenomenon in Bi2 Te3 topological quantum dots, remarkably observed at room temperature.